Pemanfaatan Ampas Tebu Dan Daun Kelor Sebagai Media Tambahan Untuk Produktivitas Jamur Tiram Putih (Pleurotus ostreatus ) - Sari, Riska Mela; , Dra. Suparti, M.Si (2017)
White oyster mushroom (Pleurotus ostreatus) is one of the fungus that grows on the surface of a rotted tree trunk. Terms grow oyster mushroom is the content of protein, lignin, cellulose and hemicellulose. Sugar cane have main content of lignocellulose and moringa leaves contain high amino acids. The purpose of this research is to know effect of addition dregs of sugar cane and moringa leaves on the growth of white oyster mushroom. This research was prepared with complete randomized design (RAL) 2 factorial, 16 treatment and 2 replication. Factor 1 moringa leaves: (K0) 0 g, (K1) 50 g, (K2) 150 g, and (K3) 250 g. Factor 2 sugar cane: (Tb0) 0 g, (Tb1) 50 g, (Tb2) 150 g, and (Tb3) 250 g. The parameters measured were the rate of spreading of mycelium, the amount of body away, and the wet weight of white oyster mushroom. Data were tested using one way anava. The results showed that the most rapid rate of mycelium growth in K0Tb3 treatment (0 moringa leaves and 250 g sugar cane) was 28 days. The largest number of fruit body in the treatment of K0Tb3 (0 moringa leaves and 250c sugar cane) was average 17.75. The highest wet weight in the K0Tb3 treatment (0 moringa leaves and 250 g sugar cane) was average 302.5 g. This shows that the nutrient content in moringa leaves and sugar cane can give effect to the productivity of white oyster mushroom. Keywords: Pleurotus ostreatus, moringa leaves, sugar cane, productivity of white oyster mushroom